Implication of glycogen synthase kinase 3 in diabetes-associated islet inflammation. Issue 1 (January 2020) - Pitasi, Caterina Luana; Liu, Junjun; Gausserès, Blandine; Pommier, Gaëlle; Delangre, Etienne; Armanet, Mathieu; Cattan, Pierre; Mégarbane, Bruno; Hanak, Anne-Sophie; Maouche, Kamel; Bailbé, Danielle; Portha, Bernard; et al.
Abstract : Islet inflammation is associated with defective β cell function and mass in type 2 diabetes (T2D). Glycogen synthase kinase 3 (GSK3) has been identified as an important regulator of inflammation in different diseased conditions. However, the role of GSK3 in islet inflammation in the context of diabetes remains unexplored. In this study, we investigated the direct implication of GSK3 in islet inflammation in vitro and tested the impact of GSK3 inhibition in vivo, on the reduction of islet inflammation, and the improvement of glucose metabolism in the Goto-Kakizaki (GK) rat, a spontaneous model of T2D. GK rats were chronically treated with infra-therapeutic doses of lithium, a widely used inhibitor of GSK3. We analyzed parameters of glucose homeostasis as well as islet inflammation and fibrosis in the endocrine pancreas. Ex vivo, we tested the impact of GSK3 inhibition on the autonomous inflammatory response of non-diabetic rat and human islets, exposed to a mix of pro-inflammatory cytokines to mimic an inflammatory environment. Treatment of young GK rats with lithium prevented the development of overt diabetes. Lithium treatment resulted in reduced expression of pro-inflammatory cytokines in the islets. It decreased islet fibrosis and partially restored the glucose-induced insulin secretion in GK rats. Studies in non-diabetic human and rat islets exposed to inflammatory environment revealed the direct implication of GSK3 in the islet autonomous inflammatory response. We show for the first time, the implication of GSK3 in islet inflammation and suggest this enzyme as a viable target to treat diabetes-associated inflammation.